2015
DOI: 10.1371/journal.pone.0142625
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Reactive Human Single-Chain Antibody for Detection of Major Fish Allergens, Parvalbumins, and Identification of a Major IgE-Binding Epitope

Abstract: Fish allergy is associated with moderate to severe IgE-mediated reactions to the calcium binding parvalbumins present in fish muscle. Allergy to multiple fish species is caused by parvalbumin-specific cross-reactive IgE recognizing conserved epitopes. In this study, we aimed to produce cross-reactive single chain variable fragment (scFv) antibodies for the detection of parvalbumins in fish extracts and the identification of IgE epitopes. Parvalbumin-specific phage clones were isolated from the human ETH-2 phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…An NMR structural and dynamics study of Gad m 1 revealed that its structure and the accessibility of putative IgE epitopes are similar to those of other parvalbumin types 14 . In a recent study, an interaction between Gad m 1 and the scFv fragment of the antibody was established using a 1 H- 15 N HSQC chemical shift perturbation method 15 .…”
Section: Introductionmentioning
confidence: 99%
“…An NMR structural and dynamics study of Gad m 1 revealed that its structure and the accessibility of putative IgE epitopes are similar to those of other parvalbumin types 14 . In a recent study, an interaction between Gad m 1 and the scFv fragment of the antibody was established using a 1 H- 15 N HSQC chemical shift perturbation method 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Both the above-mentioned studies by Nardelli et al and Ebner et al reported that T haplogroup was associated with a risk of obesity in Caucasians from Southern Italy and Austria, respectively, whereas our study showed that J haplogroup was associated with obesity in Arabs from Qatar. It is interesting to note that J and T are sister haplogroups and share polymorphisms 14 , such as MT:4216 T > C, which was significantly correlated with risk of obesity in our study (Table 4 ). However, the frequency of haplogroup T was not significantly different between our study groups with and without obesity (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…A novel mitochondrial tRNA Cys mutation at MT:5802A > G observed in 3 matrilineal relatives has been attributed as the probable cause for obesity in the family with matrilineally inherited obesity 13 . Furthermore, the mitochondrial haplogroup T has been suggested to increase the risk of obesity in 2 independent association studies on Austrian 14 and Southern Italian 15 populations. Maternal haplogroups X and H have been proposed to reduce the risk of obesity in Caucasians of northern European origin in the United States (US) 16 as well as in Arabs living in Kuwait 17 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable approach to the present study had been used by previous studies in an attempt to isolate scFv recognizing parvalbumin allergen from various species of fish (Bublin et al 2015). For that purpose, the group carried out three sequential panning on cod, carp and rainbow-trout parvalbumins, respectively.…”
Section: Resultsmentioning
confidence: 99%